DUALISM-DYCOTOMIC PARADIGM IN ISLAMIC EDUCATION - Zaini Gunawan (PEDAGOGIK : JURNAL PENDIDIKAN, 2016)
Islamic education has spawned two contradictory patterns of thought. Both have different forms, both in material aspects, the educational system, or in the form of institutional though. Two models are pat- terned traditionalist Islamic education, the which emphasizes the de- velopment of doctrine-normative aspects that growing niche to exclu- sive-apologetic. The second model of Islamic education is patterned modernist, Whose development is known to start losing fundamental spirits. The emergence of two educational models, the resulting in ambivalence orientation of Islamic education, the which one is the negative impact of dualism-dichotomoy paradigm in the education sys- tem in Indonesia, especially in the Islamic education system.